"The Legend of Nakhoda Ragam" in the Malay World and Its Link to Penang's Early History: ("Legenda Nakhoda Ragam" di Alam Melayu dan Hubungannya dengan Sejarah Awal Pulau Pinang) (Malay Literature, 2020)
The Malay World has produced many legends about extraordinary people such as rulers, nobles, warriors and the like. Patih Gajah Mada and Hang Tuah are examples of such legendary figures who possess a variety of extraordinary abilities and who are proudly regarded as idols of the community that produced them. Nevertheless, there are many other legendary figures who are not yet well known within the community but who have played no less than an important part in the history of the nation. Legends do not tell the life stories of ordinary persons; they showcase very special events associated with particular figures, which are then told and retold many times again. This article will discuss "Legenda Nakhoda Ragam" [The Legend of Nakhoda Ragam], which is well known in Brunei Darussalam, and his extraordinary adventures as a traveller in the Malay World, including his link to the founding of Pulau Pinang (Penang). Based on notes by Vaughan (1857), Nakhoda Ragam was a trader who often sailed between Lingga and Kedah. There was only one island between these two places that was attractive for him to anchor at, which he named "Pulo Ka Satu" (later Pulau Pinang or Penang). Nakhoda Ragam was also said to have founded several other places here, among them "Pulo Kindi", "Bayan Lepas", "Gerattah Sangkol", "Pulo Bittong" and "Puchut Muka", which all still exist today. This article presents evidence regarding the presence of this figure and his connection to the early history of Penang.Keywords: Nakhoda Ragam, legends, Brunei Darussalam, Penang